ECONOMIC FACTORS OF RURAL AREA DEVELOPMENT OF THE REGION, FINANCIAL SOURCES AND HUMAN RESOURCES - Ravlić, Sanela; Glavaš, Jerko; Vojinović, Zeljko (Economics of Agriculture, 2020)
The complexity of borders and border area in terms of European Union, cohesion policy, implementation of cross-border program 2007-2013 in urban and rural areas of Hungary and Croatia, monitoring the impact of invested funds and their comprehensiveness, the attitude of beneficiaries of infrastructural and human resources development projects are discussed in this paper. All in the light of given possibilities and untapped opportunities that can bring significant benefits to this area. The primary survey is conducted in the observed area after the implementation of all approved cross-border projects. Besides, available data sources and implemented research in the cross-border area of Hungary and Croatia are also discussed. The paper seeks to contribute to the discourse on the subject of monitoring the overall impact of the implemented activities in the cross-border area because there are no similar studies that comprehensively approach this complex problem for areas of cross-border cooperation in the European Union.